The influence of travel distance and transport operators objectives on fares, transport quality and generalised transport costs - Finn Jørgensen; Pål Andreas Pedersen (University of Kent, Department of Economics, 2001)
A theoretical model is adopted in order to examine optimal fare and optimal quality of supply schemes for a transport operator. The analysis shows how fares and quality of supply are related to travel distance and to the transport operator's weight on profit versus consumer surplus. Under reasonable assumptions imposed on the actual functions, it is found that the more weight the operator gives to profits, the higher the fare level and the higher the generalised travel costs. How the operator's objectives influence the quality of transport and how travelling distance affects fares, quality of transport and generalised travel costs are ambiguous, and depend on the initial restrictions placed on the actual functions. The paper then investigates how different additional restrictions imposed upon the functions influence the results. The paper also examines the special case in which the quality of transport is exogenous to the transport operator. One important result then is that higher demands towards the transport operator regarding the quality of the transport supply do not necessarily reduce the transport users' generalised travel costs.
Keywords: L2; L9; R4; 330; Travel distance; operators' objectives; optimal fare; optimal quality; generalised costs; Personenverkehr; Fahrpreis; Transportkosten; Produktqualität; Theorie